Doing criminological research - Davies, Pamela, 1962-; Francis, Peter, 1968-; Jupp, Victor (Los Angeles, [Calif.] ; London : SAGE, 2011)
This is a highly practical examination of the key issues regarding the practices and principles of research methods contextualised within studies of crime and criminal justice.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Criminology -- Research